Peripheral skin cooling during gravitational challenges in parabolic flight – experimental protocol, implementation, and case study of the CoolFly experiment - Bothe, Tomas L.; Heinz, Viktor; Pilz, Niklas; Fesseler, Leon; Patzak, Andreas; Bruckstein, Renana; Nordine, Michael; Gunga, Hanns-Christian; Opatz, Oliver (Frontiers in Physiology, 2025)
ObjectiveEnsuring cardiovascular stability is critical for the lasting and prosperous success of human spaceflight. Astronauts are exposed to dynamic acceleration profiles and prolonged changes of gravity which pose serious acute and long-term health risks. Parabolic flight is a model for gravity induced cardiovascular instability. In this proof-of-concept, we aim at analyzing the feasibility and effectiveness of peripheral cooling (PC) as a countermeasure during parabolic.MethodsIn this study, we employed a cross-over trial to investigate the effectiveness of PC in enhancing cardiovascular tolerance during gravitational changes simulated via parabolic flight. Continuous, non-invasive blood pressure, heart rate, peripheral oxygenation and brain oxygenation, peripheral blood flow, as well as skin and brain temperature were assessed. This study is a proof-of-concept for experimental feasibility and qualitative effectiveness of PC during parabolic flight.ResultsOur case study data showed reductions in heart rate of 10.0% (6.79 bpm) and reduced changes in heart rate during gravitational changes (standard deviation 12.55 vs. 10.37 bpm). Further, we observed reduced blood pressure reactions to altered gravity (−20/+39 mmHg vs. −9/+8 mmHg), with minimal changes in skin (0.27°C) and brain core temperature (0.14°C) as well as reduced changes in micro-perfusion comparing PC with control.ConclusionThis proof-of-concept study demonstrates that peripheral cooling is feasible during parabolic flight and may attenuate cardiovascular responses, as indicated by reduced heart rate and blood pressure fluctuations. These preliminary findings support further controlled studies to assess PC as a non-invasive countermeasure to changes in gravitation.